2006
DOI: 10.1111/j.1365-2796.2006.01616.x
|View full text |Cite
|
Sign up to set email alerts
|

Apo B versus cholesterol in estimating cardiovascular risk and in guiding therapy: report of the thirty‐person/ten‐country panel

Abstract: Abstract. Barter PJ, Ballantyne CM, Carmena R,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
334
0
8

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 407 publications
(359 citation statements)
references
References 109 publications
12
334
0
8
Order By: Relevance
“…Similar to non-HDL-C, it has been suggested that measurement of plasma ApoB levels is a better predictor of CHD risk than LDL-C [86][87][88][89] and concentrations less than 90 mg/dl may be considered an alternative secondary target for high-risk patients by the ATP III and CMA/Canadian guidelines [74,90]. Non-HDL-C atherogenic lipoproteins contain ApoB, and both measurements correlate to increased CHD risk [72,86], although the concordance of this in various population distributions remains unclear [87,91].…”
Section: Apob-100mentioning
confidence: 99%
See 4 more Smart Citations
“…Similar to non-HDL-C, it has been suggested that measurement of plasma ApoB levels is a better predictor of CHD risk than LDL-C [86][87][88][89] and concentrations less than 90 mg/dl may be considered an alternative secondary target for high-risk patients by the ATP III and CMA/Canadian guidelines [74,90]. Non-HDL-C atherogenic lipoproteins contain ApoB, and both measurements correlate to increased CHD risk [72,86], although the concordance of this in various population distributions remains unclear [87,91].…”
Section: Apob-100mentioning
confidence: 99%
“…Similar to non-HDL-C, it has been suggested that measurement of plasma ApoB levels is a better predictor of CHD risk than LDL-C [86][87][88][89] and concentrations less than 90 mg/dl may be considered an alternative secondary target for high-risk patients by the ATP III and CMA/Canadian guidelines [74,90]. Non-HDL-C atherogenic lipoproteins contain ApoB, and both measurements correlate to increased CHD risk [72,86], although the concordance of this in various population distributions remains unclear [87,91]. Measurement of ApoB is thought by some to provide a more accurate assessment of lipoprotein atherogenicity than non-HDL-C [86][87][88][89] because unlike non-HDL-C, which measures the cholesterol content of particles, ApoB provides a direct assessment of atherogenic particle number.…”
Section: Apob-100mentioning
confidence: 99%
See 3 more Smart Citations